Analisa Pendugaan Laju Erosi Dengan Menggunakan Model Agricultural Non Point Source Pollution (AGNPS) di Sub Das Lesti Kabupaten Malang - Kasyful Haq, Muhammad Fariz; Sholichin, Moh; Asmaranto, Runi (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Changes in landuse and the topographic are undulating and hilly with a slope of 8-45%, as well as the intensity of precipitation impacts on increased erosion rates in sub-watershed Lesti area. Continuous erosion of land causes shallows rivers in Sub-watershed Lesti. An analysis and mapping of the greater existential rates on erosion and sedimentation along with the erosion of sub-watershed Lesti as well as land conservation efforts to reduce the effects of such erosion.Calculations using a model Agricultural Non-Point Source Pollution (AGNPS) obtained an average watershed erosion rate of 163,119 tons / ha / year. The results analysis of the danger erosion levels and area based on erosion danger index by hammer (1981) is obtained with a low level index (<1) 13,770 km2, a moderate level (index 1-4) 13,521 km2, a high level (index 4-10) 14,623 km2, and an exorbitant level (index >10) 16,342 km2. Based on sediment delivery ratio (SDR), results of sediment are 144,820.54 tons / year or 120,683.96 m3 / year. The conservation of land to reduce the rate of erosion are carried out in several ways, either by using vegetative andÂ  mechanical methods.